Modelling celullar communication with scale-free networks - Radu, Dobrescu (J Med Life, 2008)
The paper proposes a model that brings to light the characteristics of several complex systems having similar scale-free network architecture. The properties of this kind of network are compared with those of other methods which are specific for studying complex systems: nonlinear dynamics and statistical methods. We place particular emphasis on scale-free network theory and its importance in enhancing the framework for the quantitative study of complex biological systems. The advantages and limits in understanding the structure of cellular signaling networks of this model are finally discussed.